Visceral leishmaniasis in Brazil: revisiting paradigms of epidemiology and control Leishmaniose visceral no Brasil: revisitando os paradigmas da epidemiologia e controle - Filipe Dantas-Torres; Sinval Pinto Brandão-Filho (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
In the last 20 years, despite the known underestimation of cases, Brazil registered a marked increase in the incidence of visceral leishmaniasis. The main goal of this review is to reflect on some aspects of this zoonosis in Brazil and also to encourage the discussion in order to find more viable, effective and affordable strategies to be implemented by the Brazilian Leishmaniasis Control Program. The current situation of visceral leishmaniasis in Brazil might be seen as a paradox: the most important aspects of the disease are known, but so far the control of this disease has not yet been achieved. The current control strategies have not been able to prevent the geographical expansion, and even a rise in the incidence and lethality of visceral leishmaniasis. There is a need not only for a better definition of priority areas, but also for the implementation of a fieldwork monitoring system to the disease surveillance that could permit a further evaluation of the control program in areas where visceral leishmaniasis is endemic. Nos últimos 20 anos, apesar da conhecida subestimação de casos, o Brasil registrou um marcado aumento na incidência da leishmaniose visceral. O principal objetivo desta revisão é refletir sobre alguns aspectos desta zoonose no Brasil e também encorajar a discussão a fim de encontrar novas estratégias, mais viáveis e efetivas, para serem implementadas no Programa Brasileiro de Controle das Leishmanioses. A situação atual da leishmaniose visceral no Brasil pode ser vista como um paradoxo: os aspectos mais importantes da doença são conhecidos, mas o controle desta doença ainda não foi conseguido. As estratégias de controle atuais não têm sido capazes de prevenir a expansão geográfica, além do aumento da incidência e da letalidade da leishmaniose visceral. Existe a necessidade de uma melhor definição das áreas prioritárias, mas também da implementação de um sistema de monitoramento das atividades dirigidas para o controle e vigilância epidemiológica, o que poderia permitir melhor avaliação do programa de controle nas diversas regiões do Brasil.